Media Baru and Wacana Sains: Isu Pengklonan melalui Blog dan Akhbar di Malaysia (New Media and Science Discourse: Cloning Issue through Weblogs and Press in Malaysia) - Adnan Hussien; Hamidah Abd. Hamid; Siti Hajar Abd. Aziz (Kajian Malaysia, 2006)
The developments of latest communication technology, especially webbased applications such as weblogs, have changed the media landscape. In countries with controlled media system, the emergence of weblogs provides an alternative medium to those who want to disseminate views normally suppressed by the mainstream media. Issues deemed sensitive by the local media seldom get due coverage. Even if there is coverage, it is presented from the perspective that is consistent with the views and ideology of the elite and the government. Hence, this paper examines and discusses the coverage, the discussion and the debates about scientific issues, especially cloning, through weblogs. Departing on the premise that blogging offers a relatively wider public sphere than the print media; discourses on cloning issues in the two media will take on different forms. This paper evaluates how bloggers on cloning issues use the openness and freedom of weblogs to voice and disseminate their views and compares it to similar discourse in Malaysian print media.